GAMBARAN PRAKTIK/KEBIASAAN KELUARGA TERKAIT DENGAN KEJADIAN PNEUMONIA PADA BALITA DI UPT PUSKESMAS SIGALUH 2 BANJARNEGARA - Puji Rahayu (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Community health centers Sigaluh 2 is one of the community health center in Banjarnegara district with some 139 cases of pneumonia in 2015 and reported one infant died. The purpose of this study to describe the practice of family of children on the prevention of pneumonia in the incidence of pneumonia in children under five years in the work area community health center Sigaluh 2 Banjarnegara district. This research is a descriptive study using cross sectional design. The sampling technique using simple random sampling totaling 88 respondents. Respondents were interviewed using a questionnaire. Data were analyzed using frequency distribution and bivariate analysis using chi square test. Results are displayed in the form of: respondents who use fuel wood as cooking fuel (8.0%), the habit of using mosquito coils (4.5%), in every family found family members who smoke at home (100%), respondents have a habit of not opening the bedroom window, especially in the morning (11.9%), respondents have the habit of not opening the living room window, especially in the morning (18.2%), respondents said rarely mop the floor (11.4%), respondents rarely sunning mattresses and pillows were 13.6% and 9.1% of respondents said waiting children recover by itself when the common symptoms of pneumonia or traditional medicine is only done at home. Advice for people in the region of community health centers Sigaluh 2 to get used to smoke outside the house, open the windows especially in the morning, mopping floors and sunning mattress/pillow regularly and promptly bring the child to the health service if found symptoms of pneumonia in children.